Antioxidant Peptides From Protein Hydrolysate of Marine Red Algae Eucheuma cottonii: Preparation, Identification, and Cytoprotective Mechanisms on H2O2 Oxidative Damaged HUVECs - Sun, Kun-Lai; Gao, Min; Wang, Yue-Zhen; Li, Xue-Rong; Wang, Peng; Wang, Bin (Frontiers in Microbiology, 2022)
In order to screen natural antioxidants with low toxicity for treating chronic diseases and food spoilage caused by excessive of reactive oxygen species (ROS), the algal proteins ZD10 and ZD60 precipitated with 10% and 60% (NH4)2SO4 were extracted from red algae Eucheuma cottonii and hydrolyzed using five proteolytic enzyme, and the papain hydrolysate of ZD60 showed the best DPPH radical scavenging rate (25.9 ± 0.24%) among all protein hydrolysates. Subsequently, six antioxidant peptides (EP1-EP6) were isolated from the papain hydrolysate of ZD60 by ultrafiltration and chromatography methods. The amino acid sequences of EP1-EP6 were identified as Thr-Ala (EP1), Met-Asn (EP2), Tyr-Ser-Lys-Thr (EP3), Tyr-Ala-Val-Thr (EP4), Tyr-Leu-Leu (EP5), and Phe-Tyr-Lys-Ala (EP6) with molecular weights of 190.21, 263.33, 497.55, 452.51, 407.51, and 527.62 Da, respectively. EP3, EP4, EP5, and EP6 showed strong scavenging activities on DPPH radical, hydroxyl radical, and superoxide anion radical. Moreover, EP4 and EP5 could significantly protect HUVECs from H2O2-induced oxidative damage, through improving cell viability (148.09% and 130.51% of model group) and increasing the levels of antioxidant enzyme system including SOD and GSH-PX to reduce the level of ROS (60.51% and 51.74% of model group) and malondialdehyde (75.36% and 64.45% of model group). In addition, EP4 and EP5 can effectively inhibit H2O2-induced apoptosis through preventing HUVECs from early apoptosis to late apoptosis. These results indicated that the antioxidant peptides, especially EP4 and EP5, derived from E. cottonii could serve as natural antioxidants applied in the nutraceutical and pharmaceutical products.